Exploring the generic skills required for the employability and professional wellbeing of Pakistani Millennials: The employers' perspective - Iqbal, Jawad; Shaikh, Aliya Ahmad; Jamal, Warda Najeeb; Akhtar, Kalsoom; Rahim, Rabia; Kousar, Shazia (Frontiers in Psychology, 2023)
Purpose – This study aims to elucidate the employers’ perspectives on the key generic employability skills which would enable the professional well-being of Pakistani Millennials, once they enter the job market after acquiring a University degree. Design/methodology/approach – An exploratory qualitative inquiry was deployed for this study which involved two panel-based discussions. The respondents of each panel discussions were invited through the platforms of the Bahawalpur Chamber of Commerce and Industry (BCCI), and Chamber of Commerce Rahim Yar Khan. As the names suggest, these Chambers of Commerce are operated in two important cities of Southern Punjab, Pakistan. Moreover, the data gathered through panel discussions were analyzed using the thematic analysis suggested by Braun & Clarke (2006), and Maguire & Delahunt (2017). Findings – The findings of the study reveal a total of 10 key generic employability skills (based on various soft and hard skills) which the employers consider to be essential for the professional well-being of Pakistani Millennial graduates. Practical implications – The paper produces implications for the employability stakeholders, including government and academia for a much-needed shift from a mere subject-based curriculum to a skill-oriented curriculum and training in the Universities, particularly in the region of Southern Punjab, and all across Pakistan as well. Originality/value – The identification of employability skills, with the help of employers, for entry-level graduate jobs, serves as an important ground for the unemployed Millennial youth (born between 1982-2001) of Pakistan to overcome their employability skills deficit by acquiring those skills which are in demand by the employers, particularly in the post-COVID times of ‘new normal. Surely, this would not only assist their market penetration in the local and global markets but also, would be beneficial for their professional well-being and sustainable employment. Limitations -The findings of the study portray the employers' perspectives who were based in Southern Punjab, Pakistan, only. Thus, the geographical scope of the study can be broadened by building a consensus on the needed skills by employers of various industries operating in different regions of Pakistan.